Prognostic Value and Immunological Role of KIFC1 in Hepatocellular Carcinoma - Li, Dan; Yu, Tao; Han, Jingjing; Xu, Xu; Wu, Jie; Song, Wei; Liu, Gang; Zhu, Hua; Zeng, Zhi (Frontiers in Molecular Biosciences, 2022)
As one of the members of the kinesin family, the role and potential mechanism of kinesin family member C1 (KIFC1) in the development of liver hepatocellular carcinoma (LIHC), especially in the immune infiltration, haven’t been fully elucidated. In this study, multiple database and immunohistochemistry were employed to analyze the role and molecular mechanism including immune infiltration of KIFC1 in LIHC. Generally, KIFC1 mRNA expression was overexpressed in LIHC tissues than normal tissues, and its protein was also highly expressed in the LIHC. KIFC1 mRNA expression was correlated with tumor grade and TNM staging, which was negatively correlated with overall survival and disease-free survival. Moreover, univariable and multivariate cox analysis revealed that up-regulated KIFC1 mRNA is an independent prognostic factor for LIHC. KIFC1 promoter methylation level was negatively associated with KIFC1 mRNA expression and advanced stages and grade in LIHC. Different methylation sits of KIFC1 had a different effect on the prognosis of LIHC. Specifically, KIFC1 mRNA expression level showed intense correlation with tumor immunity, such as tumor-infiltrating immune cells and immune scores as well as multiple immune-related genes. Moreover, KIFC1 co-expressed with some immune-checkpoints and related to the responses to immune-checkpoint blockade (ICB) and chemotherapies. Significant GO analysis showed that genes correlated with KIFC1 served as catalytic activity, acting on DNA, tubulin binding, histone binding, ATPase activity, protein serine/threonine kinase activity. KEGG pathway analysis showed that these genes related to KIFC1 are mainly enriched in signal pathways such as cell cycle, spliceosome, pyrimidine metabolism, and RNA transport. Conclusively, KIFC1 was up-regulated and displayed prognostic value in LIHC. Moreover, KIFC1 may be involved in the LIHC progression partially through immune evasion and serve as a predictor of ICB therapies and chemotherapies.